Investigation of Methicillin Resistance and Panton-Valentine Leukocidin in Staphylococci Isolated from Bovine Mastitis - Gezgen, Cansu; Seker, Esra (Acta Scientiae Veterinariae, 2016)
Background: Mastitis, which is inflammation of the mammary gland, is among the most important diseases in dairy herds resulting in reductions of milk yield and milk quality. Although several groups of microorganisms have been reported as etiological agents of mastitis, Staphylococci are the most frequently isolated bacteria from bovine mastitic milk samples. The aim of this study was to isolate the Staphylococcus species from bovine mastitis, investigate the mecA ve pvl genes in isolated species by PCR and determine the antibiotic resistance of methicillin resistant strains to some antibiotics commonly used in veterinary field. Materials, Methods & Results: In the present study, 972 half-udder milk samples (n = 757 CMT positive, n = 215 CMT negative) were used from 251 lactating cows from 34 different enterprises located center town and villages of Ödemiş, İzmir. Ten microliters of each milk sample was inoculated onto Columbia blood agar, containing 7% of sheep blood and incubated under aerobic conditions for 24-48 h at 37°C. The certain identification of Staphylococcus isolates was achieved using Crystal™ Identification Systems Gram-Positive ID kit. Bacterial DNAs were extracted from all strains using boiling method and strains were screened for the presence of 16S rDNA, mecA and pvl genes by PCR. The antimicrobial resistance of MRS species was determined by using disc diffusion method. A total of 182 (18.72%) Staphylococcus strains were isolated from 972 half-udder milk samples. Of 182 Staphylococcus strains, 137 (75.27%) and 45 (24.73%) were detected as CPS and CNS, respectively. Among the 11 different Staphylococcus species, S. intermedius (42.30%) was the most common species isolated, followed by S. aureus (32.97%) and S. saprophyticus (10.99%). The mecA positivity was found in only 4 (2.2%) S. intermedius strains, while pvl toxin gene was determined in none of the strains. Four MR S. intermedius strains were resistant to oxacillin and cefoxitin. The resistance was also found to erythromycin (50%), rifampicin (25%), gentamicin (25%), tetracycline (25%) and trimethoprim/sulfamethoxazole (25%) in the isolates. Discussion: In this study, S. intermedius had the highest isolation rate and this finding was considered remarkable. Generally, in mastitis diagnostics all CPS isolates are classified as S. aureus. In our study, the certain identification of all CPS may explain the high isolation rate of S. intermedius. The sampling method may also be the reason of higher isolation rate for S. intermedius in accordance with the most common ones causing mastitis. All of mecA positive strains were S. intermedius and this was the another remarkable finding of our study. Because similar result was seen in only one study from Korea, while the investigation finding related to MR S. intermedius was not determined in Turkey. However, the mecA positivity found in our study was lower than the other author’s isolation rate. The difference between the sample size, geographical variations and diversity in strains may be the causes of this discrepancy. It was investigated pvl toxin gene in 182 Staphylococcus strains by PCR and found this gene in none of strains. According to this finding, it was considered that pvl gene may have not an efficient role in the pathogenesis of mastitis in terms of sampled animals and sampling area. Antibiotic resistance of 4 MR S. intermedius strains against various antibiotics commonly used in Turkey was investigated. Of methicillin resistant strains, 2, 1 and 1 were resistant to 3, 6 and 5 antibiotics, respectively. It was considered that geographical differences, number of tested isolates and diversity in MR strains may be effective on the antibiotic resistance levels. This is the first study showing the presence of mecA gene in S. intermedius strains isolated from bovine mastitic milk samples in Turkey.